An Assessment of Sagittal Condylar Position of TMJ Dysfunction in Centric Occlusion by Using Cone Beam Computed Tomography - Lamia H Al-Nakib; Ako O Abdullah; Saeed A Abd Al-Kareem; Sangar H Ali (College of Dentistry/ University of Baghdad, 2016)
Background: Temporomandibular joint (TMJ) is a compound articulation formed from the articular surfaces of the temporal bone and the mandibular condyle.CBCT imaging of TMJ is that it allows accurate measurements of the volume and surface of the condyle. The aim of the study is to assess the sagittal position of mandibular condyle in patients with temporomandibulardysfunction using Cone Beam Computed Tomography in centric occlusion. Materials and Methods: CBCT images for all patients were obtained in an upright position using New Tom Giano CBCT with different field of view (11 x 8), (11 x 5), and (8 x 8) and exposure factors was changed accordingly using NNT version 5.1 software for sagittal reconstruction, anterior, superior and posterior joint spaces was measured. Results: There was a significant change in the anterior, posterior and superior joint spaces when compared to normal functioning TMJ. The sagittal position of the condyle in glenoid fossa could be affected by TMJ dysfunction and it would be positioned centrally but slightly inferior to the normal position according to the results of this study. There was no significant difference in the sagittal condylar position in glenoid fossa between sexes. There was significant difference in the value of anterior, posterior and superior TMJ spaces between right and left sides of the mandible in both normal cases and TMJD. Conclusion: Sagittal section of Temporomandibular joint revealed that TMJ dysfunction affects the joint spaces in sagittal plane. It means significant changes occur in the value of anterior, posterior and superior joint spaces when compared to normal functioning TMJ.